From talented junior to world tour cyclist: Significance of physiological and psychological characteristics - Roete, A. J.; Helmantel, A. J.; Lamberts, R. P.; Elferink-Gemser, M. T. (The Journal of Sports Medicine and Physical Fitness, 2026)
BACKGROUND: Junior cyclists` anthropometric, physiological, and psychological characteristics influence their performance. Understanding what distinguishes those who became successful from those who did not provides valuable insights for talent development. However, sample sizes in talent investigations are inherently small. Therefore, this study introduced Z-scores for analyzing talents` characteristics and identifying any discernible patterns in those who advanced to the World Tour level within their first three senior years and those who did not. The study also examined sex-based differences to determine whether sex-disaggregated analyses should be done separately for sex. METHODS: Anthropometric (height, weight), physiological (absolute, relative, VO2max, peak power output), and psychological characteristics (goal orientation, intrinsic/extrinsic motivation and self-confidence) were assessed in a cohort of 37 talented junior cyclists (27 males/10 females) aged 17-18 years. Multivariate analysis was performed to analyze sex-based differences and a novel method using Z-scores was introduced to examine characteristics influencing eventual success. RESULTS: The Permutational Multivariate Analysis of Variance (PERMANOVA) Test with post-hoc tests revealed sex-based differences in anthropometric and physiological characteristics (P<0.01), but not in psychological characteristics (P>0.05). Differential Z-Score patterns were detected, with eventually successful male attaining higher combined scores for relative VO2max and self-confidence than the less successful cyclists. No clear patterns emerged for women. CONCLUSIONS: Analysing Z-Score patterns may yield insight into the characteristics underlying talents` eventual success. Higher Z-scores across multiple characteristics in male junior cyclists indicated that well-developed physiological as well as psychological characteristics are important for advancing to the World Tour level. The pathway for women appeared to be less selective.